Prenatal presentation of an adrenocortical tumor - Jeffrey H. Schwartz; Erlyn Smith (Cancer Reports, 2022)
Abstract Background Prenatally identified suprarenal masses are most often found to be adrenal hemorrhage. The most common tumor in this situation is neuroblastoma. Case Presentation We report the case of a rare adrenocortical tumor found prenatally on ultrasound. While most patients with adrenocortical tumors present with virilizing symptoms, our patient did not have evidence of virilization and was presumed to have neuroblastoma. Conclusion Following a period of observation, our patient underwent surgical resection due to tumor growth revealing the unexpected diagnosis.